Liposomal amphotericin B for complicated visceral leishmaniasis (kala‐azar) in eastern Sudan: how effective is treatment for this neglected disease?. Issue 2 (17th January 2014) - Salih, Niven A.; van, Johan; Chappuis, François; Antierens, Annick; Mumina, Ann; Hammam, Omar; Boulle, Philippa; Alirol, Emilie; Alnour, Mubarak; Elhag, Mousab S.; Manzi, Marcel; Kizito, Walter; et al.
Abstract Objectives The aim of this study was to report the patient profile and treatment outcomes, including relapses, of patients with visceral leishmaniasis (VL) treated with liposomal amphotericin B (AmBisome) in Gedaref, Sudan. Methods AmBisome was offered to two groups of patients: primary VL patients with specific criteria (age ≤2 or ≥45 years, advanced clinical disease, pregnancy, HIV co‐infection and contraindications for antimonials) and VL relapses. AmBisome was given at a total dose of 30 mg/kg, over 10 days. Slow responders received up to 50 mg/kg. Treatment failure was confirmed parasitologically. Standardised treatment outcomes were assessed. Results Between March 2010 and June 2012, a total of 281 (74%) patients with primary VL and 98 (26%) patients with VL relapses received AmBisome (54% male, median age = 11 years, interquartile range 2–30). End‐of‐treatment outcomes for primary VL were 260 (92%) initial cure including three (1%) slow responders, three (1%) treatment failures, 14 (5%) deaths and four (1%) unknown outcomes. Outcomes for VL relapses were 92 (94%) initial cure with five (5%) slow responders, four (4%) treatment failures, one (1%) death and one (1%) unknown outcome. At 6 months, there were 19 (7%) relapses amongst primary VL and 10 (10%) VL relapses had a new relapse. Loss to follow‐up in both groups was 38%. None of the deaths that occurred during the study period was attributed to AmBisome. Conclusion AmBisome appears to be effective for initial cure of VL and the drug seems safe, but is expensive (400 USD/treatment). Sustained mechanisms to allow improved access of this expensive drug particularly in East Africa are urgently needed. Relapses and losses to follow‐up require specific investigation.